Statistical optimization of production parameters for enhanced lovastatin production from endophytic Aspergillus terreus. (October 2020) - Ravuri, Meena; Shivakumar, Srividya
Abstract: The current study attempts to statistically optimize various process parameters involved in the solid state fermentative production of lovastatin from endophytic Aspergillus terreus isolated from the apparently healthy leaves of Hibiscus rosa-sinensis . The optimization was carried out using Plackett-Burman design and central composite design of response surface methodology (RSM). Eleven variables were initially screened using Plackett-Burman design, of which, seven were found to positively influence lovastatin production. Central composite design was then implemented using the best three positively influencing variables i.e., B-group vitamins, MgSO4 and sodium acetate. The maximum lovastatin yield predicted with the optimum concentration of B-group vitamins (30%), MgSO4 (5%) and sodium acetate (30%) was 50.2605 mg/gds which was experimentally validated to be 52.5 mg/gds. The interactive effects of the positively influencing variables have been demonstrated. While there is ample literature on lovastatin production from soil A. terreus, other promising ecological niches such as plants have been least exploited for the same. This is the first report on optimization of lovastatin production from endophytic A. terreus with a significant yield that is on par with that reported so far, from soil and other endophytic fungi. Highlights: This is the first report on optimization of lovastatin production from endophytic Aspergillus terreus . Rapeseed oil cake was successfully used as substrate to enhance lovastatin production. B-group vitamins, MgSO4 and sodium acetate were found to positively influence lovastatin production. Statistical optimization resulted in a 42-fold increase in lovastatin production as compared to unoptimized conditions.